Factor Affecting the Information Sources and Communication Channels toward Pig Farmer’s Perception of African Swine Fever in Tra Vinh Province, Vietnam - N. H. Qui; B. Guntoro; S. P. Syahlani; N. T. Linh (Tropical Animal Science Journal, 2021)
The study was conducted to estimate factors affecting the information sources and communication channels that were used by pig farmers to access information about African Swine Fever (ASF) in Tra Vinh Province, Vietnam, and to determine the perception of pig farmers about ASF epidemic. The survey used the questionnaires to gather data from 150 pig farmers which was conducted in a purposive method and was analyzed by multiple logistic regression model. The respondents were pig farmers who had experienced at least one year and have been affected by ASF epidemic in raising or trading pigs and other activities of the value chain. The result showed that the decision to choose information from government extension worker as the main information resource was affected by gender, pig herd size, informal education, and formal education (p<0.01) while only gender and education affecting the choice of farming visit as their communication channel (p<0.01). When farmers can access to ASF information, they know how to anticipate the disease and deal with the outbreak. It was concluded that socio- demographic have affected the choice of information sources while only gender and formal education affected communication channels. Furthermore, when accessing information sources and communication channels, pig farmers had an awareness of basic information about ASF.